Refugia: what are they and how can they be managed?. (2nd May 2019) - Forbes, Andrew
Abstract : The word refugia appears commonly in the veterinary literature in relation to anthelmintic resistance, however it has its origins in ecology and crop protection. In the context of veterinary therapeutics, the reduction in exposure of target parasites, essentially through fewer treatments, can have bystander benefits too for non-target organisms, thus reducing the potential for environmental impact. Large refugia are intrinsic features of some livestock systems, for example extensive beef suckler farms, where treatments are typically infrequent, however on lowland sheep farms for instance, parasiticide treatments are typically more frequent and may involve both lambs and ewes, so management may need to be changed, for example through targeted selective treatment (TST), in order to enhance the refugia. Precision livestock farming and pen-side diagnostics can facilitate and extend the adoption of TST and other methods of refugia management.